1980
DOI: 10.1002/pssb.2221010112
|View full text |Cite
|
Sign up to set email alerts
|

The Lattice Structure Parameters and Configuration of Cu2+ Jahn‐Teller Centres in Tutton Salt Crystals

Abstract: EPR of Cu(H2O) 2+6 pseudo Jahn‐Teller (JT) centres in dia‐ and paramagnetic Tutton salt crystals A2M(SO4)2. 6H2O (I) with A = Rb, Cs, NH4 and M=Zn, Cu and K2M(ZrF6)2. 6H2O (II) crystals in the temperature range 300 to 4.2 K at frequencies 9.5 and 37 GHz is studied. The dynamic JT nature of Cu(H2O) 2+6 centres in the whole class of Tutton salt crystals is established basing on the results of EPR study and X‐ray data. The influence of the lowering of lattice symmetry on the configuration and properties of centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
87
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 11 publications
6
87
0
Order By: Relevance
“…A characteristic feature of the EPR of Cu(II) ions in the Tutton salt crystals is that the g-faction and hyperfine splittings are temperature dependent for admixture Cu(II) ions, whereas for the Cu(H) salts the g-factors are practically temperature insensitive with exception of (NH4)2Cu(SO4)2 • 6H2O where such dependence was reported [6,7]. The g-faction exhibit a vibronic type behaviour (pseudoJahn-Teller effect) with an averaging tendency for the two larger g-faction (gz and gy ) on heating, whereas the gx value appearing along the shortest Cu-O(9) bond only weakly increases with temperature.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A characteristic feature of the EPR of Cu(II) ions in the Tutton salt crystals is that the g-faction and hyperfine splittings are temperature dependent for admixture Cu(II) ions, whereas for the Cu(H) salts the g-factors are practically temperature insensitive with exception of (NH4)2Cu(SO4)2 • 6H2O where such dependence was reported [6,7]. The g-faction exhibit a vibronic type behaviour (pseudoJahn-Teller effect) with an averaging tendency for the two larger g-faction (gz and gy ) on heating, whereas the gx value appearing along the shortest Cu-O(9) bond only weakly increases with temperature.…”
Section: Introductionmentioning
confidence: 92%
“…6H2O crystal [11] we have found a vibronic g-factor behaviour, which is however, much weaker as compared to that found in (NH4)2Cu(SO4)2 . 6H2O [7]. We will describe this behaviour in terms of the existing models and discuss their validity in condensed Cu(II) paramagnets.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This model has been successfully used for a description of Cu(H2O)P 2 + 6 vibronic complexes behaviour in K 2 Zn(SO4 ) 2 • 6H 2 O and after a generalization by Hitchman et al [2] it was found as a good approximation in some diamagnetic Tutton salt crystals doped with Cue+ ions [3]. However, a clear deviation from predictions of the model was found in ammonium Tutton salts [4], especially in (NH4 ) 2 Mg(SO4 ) 2 • 6H 2 0 [5].…”
Section: Introductionmentioning
confidence: 99%
“…The deformation of the hexaaqua octahedra in diamagnetic salts is rather small but becomes large, due to the strong Jahn-Teller effect in Cue+ doped salts. In Cs 2 Cu(SO4 ) 2 •6H2O the molecular structure of the Cu(H20) 6-complex is known [3] …”
Section: Introductionmentioning
confidence: 99%